Responses to Hydric Stress in the Seed-Borne Necrotrophic Fungus Alternaria brassicicola - N’Guyen, Guillaume Quang; Raulo, Roxane; Marchi, Muriel; Agustí-Brisach, Carlos; Iacomi, Beatrice; Pelletier, Sandra; Renou, Jean-Pierre; Bataillé-Simoneau, Nelly; Campion, Claire; Bastide, Franck; Hamon, Bruno; Mouchès, Chloé; et al. (Frontiers in Microbiology, 2019)
The necrotrophic fungus Alternaria brassicicola causes black spot disease and is an economically important seed-borne pathogen of Brassicaceae species. Its transmission to seed is a major component of pathogen fitness, as this fungus strongly depends on this process for its dispersal and long-term survival. Recent studies, conducted with the Arabidopsis thaliana / A. brassicicola pathosystem, showed that the level of susceptibility of the fungus to water stress strongly influenced its seed transmission ability. In this study, we gained further insights into the mechanisms involved in the seed infection process by analysing the transcriptomic and metabolomic responses of germinated spores of A. brassicicola exposed to water stress. Then, the repertoire of putative hydrophilins, a group of proteins that are assumed to be involved in cellular dehydration tolerance, was established in A. brassicicola based on the expression data and additional structural and biochemical criteria. Phenotyping of single deletion mutants deficient for fungal hydrophilin-like proteins showed that they were affected in their transmission to A. thaliana seeds, although their aggressiveness on host vegetative tissues remained intact.